Comparative analysis of distribution the species of the Heteroptera of Tuva in width-zonal gradient - S. V. Kuzhuget (Acta Biologica Sibirica, 2017)
In the article, the features of the distribution of hemiptera along the width-zonal gradient are considered, which is reflected in the depression – Turan-Uyuk, Central-Tuva and Uvs-nuur, located from the north to the south. The ways of adaptation of hemiptera to the arid climate of the Ubs-nuur depression are singled out.